Minimally invasive direct coronary artery bypass in the era of percutaneous coronary intervention. Issue 2 (February 2015) - Raffa, Giuseppe M.; Malvindi, Pietro G.; Ornaghi, Diego; Citterio, Enrico; Cappai, Antioco; Basciu, Alessio; Barbone, Alessandro; Fossati, Francesca; Tarelli, Giuseppe; Settepani, Fabrizio
Abstract : Aim: Minimally invasive coronary artery bypass (MIDCAB) allows revascularization of the left anterior descending coronary (LAD) artery through a less traumatic surgical approach. However, the procedure is technically challenging and concern still exists, mainly based on graft patency. The purpose of this study is to critically evaluate short and long-term benefits of this surgical treatment. Methods: Between June 1997 and July 2012, 306 patients underwent MIDCAB on LAD. The mean age was 62 ± 10 years (range, 32–87 years) and 264 patients (86.3%) were men. Mean ejection fraction was 54%. Eighty-nine procedures (29.1%) were performed using a hybrid approach by means of MIDCAB and postoperative (60 patients, 67.4%) or preoperative (29 patients, 32.6%) percutaneous interventions on non-LAD vessels. A EuroScore more than 6 was found in 43 (14%) patients. The average follow-up time was 9.5 ± 3.2 years and was 89% complete. Results: Six patients (1.9%) required intraoperative conversion to sternotomy, whereas cardiopulmonary bypass institution after the sternotomy was necessary in one. Postoperative acute myocardial infarction occurring nine patients (2.9%), low output syndrome in four (1.3%). Postoperative mortality was 1.6% ( n = 5), and perioperative stroke rate 0.6% ( n = 2). Five and 10-year survival were 94.1 and 86.9%, respectively. Freedom from death due to cardiac events and major cardiac and cerebral events at 10 years was, respectively, 97.1 and 92.1%. Conclusions: The results confirm the favorable short and long-term results of the MIDCAB procedure. MIDCAB, in experienced centers, can represent an alternative treatment option for LAD disease.